Post-Pandemic Development: Sluggish or Rapid Recovery? - Dharendra Wardhana (Pusbindiklatren Bappenas, 2020)
The year 2020 will be recorded in world history as one of the most challenging periods. With the benefit of hindsight from previous crises, humanity will eventually (and this time hopefully) prevail. Covid-19 pandemic which has been around for a full calendar year sets a reminder and a call for us to adapt with a new mindset to embrace the new normal in our life. Not many countries can strike a delicate balance between saving lives and protecting livelihoods during this difficult time. Obviously, most developing countries have been struggling to control this seemingly intractable calamity from the first day of the outbreak. Covid-19 pandemic has sent the world one strong message, it is that we are only as safe as the most vulnerable among us. This indicates the central place of solidarity in our life. While we are predicting the emergency-authorized vaccine as the “game-changer”, estimating the outcome in the following years leads us to numerous possibilities and scenarios. Questions surrounding vaccine distribution, efficacy rate, and unintended consequences will still linger. Narrowing down the probabilities will lead us to two contrasting scenarios either growth will be propelled immediately or growth will not be accelerated due to various factors. Echoing previous editorial notes, the impact of the Covid-19 pandemic on SDGs targets (also to other global and national development plans) can be mixed. The quintessential question is on how we maintain positive outcomes when the pandemic is over and how to get back on the right track. Apparently, many development targets need to be revised and some if not most of them might not be easy to catch up with. This situation arguably sets a backdrop for “the great reset” where all development strategies need to be restarted, policies have to be scrutinized, and targets must be re-calibrated. Undoubtedly, making predictions these days is not an easy job indeed. Too many variables and events need to be taken into account so as to reflect the complex world we live in. Sophisticated statistical methods and state-of-the-art computation technology do not really guarantee accuracy. It only needs a shock which makes our prediction becomes irrelevant. Many these days acknowledge VUCA (volatility, uncertainty, complexity, and ambiguity) as inherent characteristics of modern development. This poses serious challenges for those who work as planners in various contexts. Revising our projection might increase credibility but nobody knows for how long the revised targets will remain in a dynamic setting like nowadays. The year 2020 gives a lesson that we seemingly learn the hard way. One important lesson is on finding the correct perspective in viewing government spending. For many years we have seen the dominant role of government spending in development and it becomes more prominent when the economy stagnates. However, we have also been constantly looking for a better way to increase the quality of spending and more importantly: the way we measure it. Apparently, it seems, current measurement is inextricably linked with rigid public accounting standard which does not allow much flexibility and largely fulfills an administrative purpose. Sadly, it tends to normalize the “gold standard” of government spending: “the more we spend, the better” which unfortunately reveals the downside of such a spending pattern. That explains the acceleration of absorption rate at the end of the fiscal year, anecdotes on a spending frenzy, and whimsical disbursement for the sake of spending. Alternative measurement like efficiency score needs to be introduced immediately as a replacement of current performance indicators which is merely based on the monetary-based absorption rate of the annual budget. A simplistic method of budget absorption rate might still be relevant with tangible projects like infrastructure but it might be barely sensible within the context of intangible activities such as research, studies, advisory, and other knowledge sector-related projects. In order to reduce the Covid-19 contagion, governments opt for mobility restriction which consequently causes almost entirely business activities into the hold. Travelling and MICE industries—which arguably predominates government spending on knowledge-sector as well as one of the most prioritized sectors in the economy—have been hit the hardest during the pandemic. The inefficiency problem has been rising to the surface and this time should attract more attention to policymakers and scholars. This sends an urgent call for those who are competent to develop a correct alternative to measure one’s performance. Indeed, government spending is considered as the prime mover during difficult times and plays a pivotal role to accelerate economic recovery. However, the quality of spending will determine policy effectiveness. Mobility restriction brings a corollary that practices like working from home, digital economy, and assistive technology become a new normal. Numerous companies in developed countries pledged to resume this highly efficient and environment-friendly practice even after the pandemic. Yet, we have to ponder upon this shift into the context of developing countries where the informal economy is still rampant with the labor force population entering its peak. Probably unbeknownst to many, this “inefficiency” and negative externality (air pollution, road congestion, disposed waste) somehow correlates with employment creation and significantly acts as an economic multiplier. Finding the balance between “multiplier” and “efficiency” on government spending is therefore another issue that should be on the problem-solving bucket list. With quality spending, the policy effectiveness will lead to better outcomes which hopefully will bring rapid recovery. Not only have the Covid-19 crisis taken a heavy toll on people’s lives, but it also made a dent in the global economy. Its adverse impact on jobs, livelihoods, poverty, and inequality has been reversing some of the gains that countries had made over the past few decades. To contain the damage, countries the world over have been adopting and adapting various policies to protect their populations and stabilize the economy. Problems and challenges that remain unsolved before the pandemic have been looking for solutions. Therefore, in this issue, we invite authors from diverse academic backgrounds to present their works not exclusively revolving around topics on Covid-19 pandemic but also to other important themes such as poverty (Nuryitmawan), urban planning (Sari et al), public finance (Putri), disaster mitigation (Erlinna), environment (Yazawa and Shimizu), well-being measurement (Suriadi and Kususanto), middle class (Pratomo et al), and tourism (Warganegara). We invite the readership to give us feedback on these articles and we surely welcome submissions on other topics from all fields of science in the upcoming issue.